The Clostridium difficile Infection – Daily Symptoms (CDI-DaySyms™) Patient-Reported Outcome (PRO) Questionnaire: Final Validation and Responder Thresholds. (4th October 2017) - Talbot, George H; Kleinman, Leah; Davies, Evan W; Hunsche, Elke; Roberts, Laurie; Nord, Carl Erik
Abstract: Background: Patient perspectives on their disease are undoubtedly important in clinical trials and in practice. To date, no patient-reported outcome (PRO) questionnaire assessing symptoms of Clostridium difficile infection (CDI) has been developed following FDA guidance. The CDI-DaySyms™ is a new comprehensive measure of a broad range of local and systemic CDI symptoms (not only diarrhea) that patients report as meaningful. Objectives were to: finalize the CDI-DaySyms™ items (questions); assign them to domains (concepts); evaluate the questionnaire's measurement properties; and define responder thresholds. Methods: Blinded data from a sub-study of two Phase III trials (NCT01987895 and NCT01983683) in CDI patients were analyzed following FDA guidance for validating PRO questionnaires. Patients completed the CDI-DaySyms™ daily from Day 1 until end of treatment. Items were selected for inclusion in the final questionnaire based on a range of validation analyses, input from expert clinicians, and findings from prior qualitative patient research. Responder-threshold analyses used Day-3 data to align with the rapid symptom improvement generally seen in response to CDI therapy. Results: Data were analyzed for 168 CDI patients (median age 60 years; 67.9% female; 81.5% mild/moderate, 11.3% severe, 7.1% unknown disease severity; 80.4% first CDI occurrence, 19.6% first recurrence). Three of the 13 items in the draft CDI-DaySyms™ were deleted; the remaining 10 were statistically assigned to three domains measuring different symptom concepts (Figure). Individual items in each domain correlated strongly with one another and their domain. Domain scores demonstrated acceptable consistency over time in stable patients, were sensitive to change, and correlated in expected directions with scores of other relevant symptom and disease-severity measures. Responder thresholds were defined as score changes of -1.00, -0.80, and -0.70 for Diarrhea, Abdominal, and Systemic/Other Symptoms domain scores, respectively. Conclusion: The CDI-DaySyms™ is a valid measure of diarrhea and other CDI symptoms useful in assessing response to therapy. It has good measurement properties, and with only 10 items can be easily administered in clinical trials and in practice. Disclosures: G. H. Talbot, Actelion: Board Member, Consultant and Scientific Advisor, Consulting fee; L. Kleinman, Actelion: Consultant, Research support; E. W. Davies, Actelion: Employee, Salary; E. Hunsche, Actelion: Employee and Shareholder, Salary; L. Roberts, Actelion: Consultant, Research support; C. E. Nord, Actelion: Scientific Advisor, Consulting fee